STAGES OF DEVELOPMENT OF MANAGEMENT: CHARACTERISTICS OF MANAGEMENT IN ANCIENT CHINA AND INDIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the history of the development of management in ancient times, the development of management ideas, and its specific features are reflected. Also, the demands placed on the management and the managers and supervisors by the mature thinkers of their time were expressed. Philosophical views, ancient works that contributed to the development of management, and opinions on management were briefly analyzed.